Asksia AI LOGO

Sia

tianhao24364's Question
Math
Posted 5 months ago

If f(x)=3x2+6x+2f(x)=3 x^{2}+6 x+2, find f(5)f^{\prime}(-5), using the definition of derivative. f(5)f^{\prime}(-5) is the limit as xx \rightarrow \square of the expression \square
The value of this limit is \square
Use this to find the equation of the tangent line to the parabola y=3x2+6x+2y=3 x^{2}+6 x+2 at the point (5,47)(-5,47). The equation of this tangent line can be written in the form
y=
y=\square

\square
Sign in to unlock the answer
Answer from Sia
Verified answer
Posted 5 months ago
Solution by Steps
step 1
To find the derivative of f(x)=3x2+6x+2 f(x) = 3x^2 + 6x + 2 at x=5 x = -5 , we use the definition of the derivative: f(5)=limx5f(x)f(5)x+5 f'(-5) = \lim_{x \to -5} \frac{f(x) - f(-5)}{x + 5}
step 2
We first calculate f(5) f(-5) : f(5)=3(5)2+6(5)+2=7530+2=47 f(-5) = 3(-5)^2 + 6(-5) + 2 = 75 - 30 + 2 = 47 . Thus, the limit becomes limx5f(x)47x+5 \lim_{x \to -5} \frac{f(x) - 47}{x + 5}
step 3
Now we substitute f(x) f(x) into the limit: limx5(3x2+6x+2)47x+5=limx53x2+6x45x+5 \lim_{x \to -5} \frac{(3x^2 + 6x + 2) - 47}{x + 5} = \lim_{x \to -5} \frac{3x^2 + 6x - 45}{x + 5}
step 4
We can factor the numerator: 3(x2+2x15)=3(x+5)(x3) 3(x^2 + 2x - 15) = 3(x + 5)(x - 3) . Thus, the limit simplifies to limx53(x+5)(x3)x+5=limx53(x3) \lim_{x \to -5} \frac{3(x + 5)(x - 3)}{x + 5} = \lim_{x \to -5} 3(x - 3)
step 5
Evaluating the limit as x5 x \to -5 : 3(53)=3(8)=24 3(-5 - 3) = 3(-8) = -24 . Therefore, f(5)=24 f'(-5) = -24
step 6
The slope of the tangent line at the point (-5, 47) is m=24 m = -24 . We can use the point-slope form of the line: yy1=m(xx1) y - y_1 = m(x - x_1) where (x1,y1)=(5,47) (x_1, y_1) = (-5, 47)
step 7
Substituting the values into the point-slope form: y47=24(x+5) y - 47 = -24(x + 5) . Simplifying gives y=24x120+47 y = -24x - 120 + 47 or y=24x73 y = -24x - 73
Answer
The derivative f(5)=24 f'(-5) = -24 and the equation of the tangent line is y=24x73 y = -24x - 73
Key Concept
The derivative represents the slope of the tangent line to the curve at a given point.
Explanation
We used the definition of the derivative to find the slope at x=5 x = -5 and then applied the point-slope form to derive the equation of the tangent line.

Not the question you are looking for? Ask here!

Enter question by text

Enter question by image

Unlock Smarter Learning with AskSia Super!

Join Super, our all-in-one AI solution that can greatly improve your learning efficiency.

30% higher accuracy than GPT-4o
Entire learning journey support
The most student-friendly features
Study Other Question